Power Scaling Methods for RF Excitation Fields in MRI Systems - Seon-Eui Hong; Giuseppe Carluccio; Christopher M. Collins; Hyung-Do Choi; Sukhoon Oh (Journal of Electromagnetic Engineering and Science)
In this paper, we analyze the homogeneity of the transmitted radiofrequency (RF) field by applying different power scaling methods ranging from low-field (12.8 MHz, 0.3 T) to high-field (298 MHz, 7.0 T) magnetic resonance imaging (MRI) systems. Homogeneity strongly depends on RF power scaling, especially in higher-field MRI. While no notable homogeneity problem is usually observed in lower-field MRI, strong center brightening occurs at a higher field, owing to shortened wavelength. In particular, the dependence of homogeneity on RF power scaling appears during the initial MRI system calibration. In this study, we evaluate the 10-g averaged specific absorption rate (SAR) to evaluate RF safety. This rate may suffer from severe phase interferences, especially in the case of higher-field MRI, due to the increased strength of the static magnetic field and the complex distribution of electrical properties in structures, such as the human head. In particular, the 10-g averaged SAR level is up to six times higher in higher-field MRI with entire-area RF power scaling than with center scaling. Overall, this study establishes the importance of accounting for MRI scan homogeneity and RF safety during MRI examinations.